Pendanaan Pihak Ketiga (Third Party Funding) Dalam Penyelesaian Sengketa Melalui Arbitrase Dan Kemungkinan Penerapannya Di Indonesia - Temenggung, Carissa T.A.; Dewi, Yetty Komalasari (UI Scholars Hub, 2023)
The Third Party Funding (TPF) concept is an alternative method of funding usually applies in the dispute resolution process. Recently, the TPF concept has often been used in the process of resolving international arbitration disputes, both commercial and investment. This paper analyses the TPF concept and practices in several states, and its possible application in Indonesia. In particular, this paper discusses efforts made to regulate the TPF both in national law of several jurisdictions and in the international level, key issues within TPF in relation to the arbitration dispute resolution, and the TPF key provisions to be considered should Indonesia decides to apply such concept within its jurisdiction.